Efeitos do fipronil sobre o metabolismo energético no fígado perfundido de rato: Hyllana Catarine Dias de Medeiros. - - Medeiros, Hyllana Catarine Dias de [UNESP] (2014)
Fipronil is an insecticide used to control parasitic infestations in animals and plants. Its mechanism of action is through inhibition of receptor γ-aminobutyric acid and the Cl- channel. In mammals, besides the central nervous system, other organs may be affected by treatment with fipronil, including the liver. The present study aimed to characterize the effects of fipronil on hepatic metabolism, through the technique of isolated perfused rat liver. Parameters related to carbohydrate metabolism in the postprandial and fasting period and also the aminoacids metabolism during fasting were evaluated. Fipronil was infused in the perfused livers in the concentration range of 10-50 μM. Oxygen consumption was monitored by polarography and in samples of effluent perfusate the production of glucose, lactate, pyruvate, urea and ammonia was quantified. In fed animals, fipronil inhibited the oxygen consumption significantly. There was increased release of glucose and lactate from the catabolism of glycogen, indicating stimulation of glycogenolysis and glycolysis. In the liver of fasted animals, fipronil inhibited the production of glucose and urea from exogenous L-alanine, whereas the production of ammonia and lactate was increased. These results indicate that the fipronil inhibits biosynthetic processes (gluconeogenesis and ureagenesis) and stimulates compensatory processes of ATP formation (glycolysis and glycogenolysis). Inhibition of oxygen consumption corroborates the suggestion that an inhibitory effect on mitochondrial respiratory activity and therefore an interference with energy metabolism is the possible mechanism of cytotoxic action of fipronil